British Women's Life Writing, 1760-1840 - Culley, A. author. aut Link
VIII, 270 p.
Keywords: British Women's Life Writing, 1760-1840 brings together for the first time a wide range of print and manuscript sources to demonstrate women's innovative approach to self-representation. It examines canonical writers, such as Mary Wollstonecraft, Mary Robinson, and Helen Maria Williams, amongst others.